PEMIKIRAN DAN PEMAKNAAN (KAJIAN SEMIOTIK) LIRIK LAGU-LAGU THE TERIGGAS OF SAMBAS KARYA MUL’AM HUSAIRI WALID - Agus Syahrani; MUHAMMAD SAIFUL HAQ (Universitas Andalas, 2013)
This study was conducted on a prominent humanist from Sambas, Pontianak, West Kalimantan to demonstrate his skill and effort in maintaining the Sambas Malay culture, especially through his singing.He is also an expert in playing the traditional Malay instruments, namely rumian, drums, violin, harp, and others. Arising from the awareness on the importance of art conservation, especially Sambas Malay culture in particular, and regional Malay culture in general, he has established a working team to train and engage the young children in playing the drums. Based on his own collection, as well as his expertise in the field of Malay arts, he was appointed as a guest writer at the Academy of Malay Studies, University of Malaya. Therefore, this study will be focusing on his involvement in the field of art of music, throughout the Province of Sambas, West Kalimantan, Indonesia to the moment he successfully sustained the production of a compact disc entitled ‘The Terrigas of Sambas’ (Ngayatte 'ge song' Mare ') which load the songs as listed below:ALO’ GALING LASSOUNG LABBANALON-ALONTA’ALLAW BINATIKANNANG URRANG TUECA’ UNCANGTANDA’ SAMBASKAPAL BELONCIK-CIK PERIOUKBATU BALLAH